2014
DOI: 10.1094/phyto-10-13-0274-r
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola in Rice Seed Using a Padlock Probe-Based Assay

Abstract: Based on 16S-23S internal transcribed spacer ribosomal DNA sequence data, two padlock probes (PLPs), P-Xoo and P-Xoc, were designed and tested to detect Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola, respectively. These PLPs were combined with dot-blot hybridization to detect X. oryzae pv. oryzae and X. oryzae pv. oryzicola individually in rice seed. Using this technique, a detection sensitivity of 1 pg of X. oryzae pv. oryzae genomic DNA was observed. The technique also facilitated the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Compared with compounds (1-3), all hydroxyls were substituted by methoxyls on the benzene rings in compounds (7)(8)(9). Interestingly, compounds (7-9) had no inhibitory effects on Xoo growth, indicating that the hydroxyls were the vital active group for the inhibitory effects on Xoo growth observed for compounds (1)(2)(3). For many inhibitors, the double bond and the hydroxyls played important roles in the anti-Xoo activity, such as sphaeropsidin A, the main phytotoxin produced by Diplodia cupressi [17], and it was reported that stilbenoids with at least one free hydroxyl group as a common structural feature suggested an association with the antimicrobial activity, such as against Bacillus subtilis and Pseudomonas syringae [18].…”
Section: Inhibitory Effects On Growth Of Xoo and The Potential Structmentioning
confidence: 96%
See 3 more Smart Citations
“…Compared with compounds (1-3), all hydroxyls were substituted by methoxyls on the benzene rings in compounds (7)(8)(9). Interestingly, compounds (7-9) had no inhibitory effects on Xoo growth, indicating that the hydroxyls were the vital active group for the inhibitory effects on Xoo growth observed for compounds (1)(2)(3). For many inhibitors, the double bond and the hydroxyls played important roles in the anti-Xoo activity, such as sphaeropsidin A, the main phytotoxin produced by Diplodia cupressi [17], and it was reported that stilbenoids with at least one free hydroxyl group as a common structural feature suggested an association with the antimicrobial activity, such as against Bacillus subtilis and Pseudomonas syringae [18].…”
Section: Inhibitory Effects On Growth Of Xoo and The Potential Structmentioning
confidence: 96%
“…Dramatically, resveratrol (1) showed the strongest antibacterial activity against Xoo (IC 50 11.67 ± 0.58 μg/mL) ( Table 2), and at 5 μg/mL, 25 μg/mL, and 100 μg/mL, the inhibiting percentage on Xoo growth was 24.66 ± 1.79, 75.84 ± 3.14, and 90.49 ± 0.28, respectively. For compounds (2)(3)(4)(5)(6), the inhibiting percentages on Xoo growth at 100 μg/mL were 89.39 ± 0.43, 78.89 ± 0.80, 82.76 ± 1.02, 54.30 ± 6.05, and 58.51 ± 3.11, respectively, and at 5 μg/mL were 16…”
Section: Antibacterial Activity Of Compounds (1-9) Against Xoomentioning
confidence: 99%
See 2 more Smart Citations
“…This process termed as the padlock probe assay has been used in the detection of many plant diseases. [87][88][89] High multiplexity and specificity of padlock probes followed by RCA also increases the popularity of its application in multiplex detection of plant pathogens. In addition, RCA has been reported to have higher specificity and be less prone to nonspecific amplification than PCR.…”
Section: Rcamentioning
confidence: 99%